Colación del manuscrito S-III-19 de las Metamorfosis de Ovidio del Real Monasterio de El Escorial - Murcia, Elena (Exemplaria Classica, 2008)
The aim of this article is to contribute to the study of the text of Ovid’s Metamorphoses by the collation of the manuscript Escorialensis S-III-19, which presents numerous readings matching, in particular, the ’no Lactancia’ family of the manuscript tradition of the above-mentioned work.